Prediction of Basketball Shooting Ability on the Basis of Anthropometric Characteristics, Wrist Range of Motion, and Strength of Upper Extremity in Elite Female Basketball Players - Nahid Adibpour; Leila Ghazaleh; Farzaneh Hatami (Islamic Azad University, Hamedan Branch, 2016)
Objective: This study aims to predict basketball shooting ability on the basis of anthropometric characteristics, wrist range of motion, and strength of upper extremity in elite female basketball players. Methods: The sample of the study included 34 female basketball players invited to attend the national team trainings. 15 subjects were playing in center and 19 subjects in guard and forward positions. Measuring tapes and standard method (ISAK) were used to measure the length of segments of dominant or shooting upper extremity. Digital dynamometer and goniometer were used to measure muscular strength and the wrist range of motion, respectively. Shooting ability of players was assessed by standard tests of free throw, three pointer and elbow shot. The research data was statistically analyzed using linear regression analysis. Results: Results showed that only forearm length variable is significantly effective on free throw shot. However, according to measures and regression coefficient, this effect was low. Conclusion: When choosing players for the guard and forward positions, coaches can necessarily ignore the stature and length of upper limb issue, and pay more attention to the other factors such as their shooting technique.